Ekonomi Gig sebagai Strategi Diversifikasi Lapangan Kerja di Era Digital: Analisis Spasial Perekonomian Indonesia Menggunakan Pendekatan Penginderaan Jauh: Ekonomi Gig sebagai Strategi Diversifikasi Lapangan Kerja di Era Digital: Analisis Spasial Perekonomian Indonesia Menggunakan Pendekatan Penginderaan Jauh - Primasrani, Byun; Akbar, Fadly Muhamad; Butar Butar, Rinald Parulian (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
The rise of the digital economy has fueled the growth of gig workers as a new driver of regional economic development in Indonesia. This study examines how gig related activities influence output of the service sector and explores their spatial spillover effects across provinces. Using the Spatial Durbin Error Model (SDEM), the analysis employs output of the service sector as the dependent variable and includes Night-Time Lights (NTL), casual non-agricultural workers, internet user percentages, provincial minimum wage, average years of schooling, and micro and small industries (IMK) output as independent variables. Results reveal that NTL, casual non-agricultural workers, and average years of schooling positively and significantly affect output of the service sector, highlighting the role of gig economy and human capital in productivity growth. Conversely, internet use shows a negative effect, indicating unequal digital utilization. Spatially, the lag of casual non-agricultural workers shows a negative spillover effect, suggesting that provinces with higher service sector output tend to attract cross-regional workers, thereby reducing labor availability in neighboring areas. Meanwhile, IMK output in adjacent provinces demonstrates a positive spillover effect, indicating complementary linkages that strengthen interregional economic activity. These findings imply that the gig economy can serve as an effective mechanism to boost regional economic output through job diversification, especially amid limited formal job opportunities. Strengthening gig-based employment ecosystems may therefore become a strategic option to sustain economic growth and promote inclusive labor market development in Indonesia.